1979
DOI: 10.1007/bf01739482
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic distribution of tubulin:Tyrosine ligase

Abstract: The post-translational addition of tyrosine to alpha-tubulin, catalyzed by tubulin:tyrosine ligase, has been previously reported in mammals and birds. The present study demonstrated that significant ligase activity was present in representative organisms from several other major vertebrate classes (chondrichthyes through reptiles) and that both substrate and enzyme from all vertebrates investigated were compatible with mammalian ligase and tubulin in the tyrosination reaction. None of the invertebrate tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…However, tubulin tyrosine-ligase was not found at this time in Tetruhymena and yeast, and only a low level, at best, was observed in sea urchins [53]. Others reported the absence of tubulin tyrosine-ligase from invertebrate tissues [54] but it was eventually shown that if the enzyme is partially purified it can be detected easily in invertebrates, even though it still was not seen in Teti-ahymena [55]. Tubulin tyrosine-ligase is now known to enjoy a wide phylogenetic distribution.…”
Section: Tubulin Tyrosine-ligasementioning
confidence: 77%
“…However, tubulin tyrosine-ligase was not found at this time in Tetruhymena and yeast, and only a low level, at best, was observed in sea urchins [53]. Others reported the absence of tubulin tyrosine-ligase from invertebrate tissues [54] but it was eventually shown that if the enzyme is partially purified it can be detected easily in invertebrates, even though it still was not seen in Teti-ahymena [55]. Tubulin tyrosine-ligase is now known to enjoy a wide phylogenetic distribution.…”
Section: Tubulin Tyrosine-ligasementioning
confidence: 77%
“…The terminal tyrosine on a-tubulin can be both removed and replaced by enzymes originally found in rat brain (3,5,6) and since found in many other tissues and species (18,46,51). Although the presence or absence of the terminal tyrosine does not seem to alter the in vitro assembly properties of tubulin (2), the fraction of tyrosinated tubulin is different in assembled and unassembled pools (53).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting detyrosinated tubulin exposes a carboxy-terminal glutamic acid and is therefore referred to as Glu-tubulin. Tubulin tyrosination is known to occur in a great variety of species ranging from humans 32 to invertebrates such as trypanosomes. 33 However, although yeast cells encode a C-terminal tyrosine (Schizosaccharomyces pombe) or a phenylalanine (Saccharomyces cerevisiae), the tyrosination cycle itself does not exist in these species.…”
Section: The Tubulin Tyrosination Cyclementioning
confidence: 99%